Evaluation of Three Important Electrode Arrays in Defining the Vertical and Horizontal Structures in 2D Imaging Surveys - M. Thabit, Jassim; S. Al-Zubedi, Ahmed (Iraqi Journal of Science, 2023)
Three important electrode arrays in 2D imaging surveys were tested in this study through synthetic model to determine which array is the most successful in defining the vertical and horizontal geological structures. These arrays are Wenner-Schlumberger, Wenner and Dipole - dipole. The numerical modeling was created through vertical fracture zone and three separate cavities surrounded by horizontal layers. The results showed that the Wenner-Schlumberger is the most suitable electrode array when both vertical and horizontal structures are present in the subsurface. It is the best in imaging the vertical and horizontal contacts and represented these structures more accurately than the Wenner and Dipole-dipole arrays.